A design of high optical efficiency wedge type light guide plate adopting twin inclined cylindrical surface. Issue 8 (17th September 2017) - Itoga, Kenji; Takaira, Kazutada; Sakai, Seiji; Fujino, Toshiaki; Satake, Tetsuya; Yuuki, Akimasa
Abstract: We propose wedge type light guide plate (LGP) adopting twin inclined cylindrical surfaces (TICS) at the incident part of a LGP. It has higher optical efficiency than conventional wedge type LGP. In dimension of LGP which the thickness of incident part is 1.5 mm and that of luminance part is 0.7 mm, the optical efficiency of wedge type LGP adopting TICS is expected to be 96% in comparison with a normal flat LGP. In addition, there is an advantage to reduce the non‐uniformity of vicinity of light emitted diodes (LEDs) by TICS reflecting light laterally. However, it is necessary that the LED centers are aligned with the intersections of TICS. The misalignment of LED causes non‐uniformity of optical profile that is slightly larger than a normal LGP. Abstract : We propose wedge type light guide plate (LGP) adopting twin inclined cylindrical surfaces (TICS) at the incident part of a LGP. The optical efficiency of this new LGP is nearly equal to that of normal flat LGP, even though the thickness of luminance part of new LGP is less than half of normal flat LGP.